Skeletal maturation and growth in children and adolescents - Lopes Machado, Dalmo Roberto (2007)
If the differences between biological age and chronological age (CA) are not taken into account, it is possible that the physical growth that is observed during adolescence may be given divergent interpretations. Bone age (BO) has been recognized as an effective indicator of biological age, and, based on this, this study investigates the repercussions of analyzing growth according to chronological age or to biological age, with a sample consisting of 233 schoolchildren aged nine to 16 years of both sexes (female=109; male=114). Bone age was determined using wrist and hand x-rays and growth by conventional anthropometry (stature, body mass and skinfolds). The results demonstrate that BA was, on average, greater than CA, and females exhibited greater variation than males. Females were more mature than males, but males had larger mean final measurements for height and body mass and smaller skinfold measurements. The greatest differences between BA and CA were observed from 13 years onwards in females and from 12 years in males, being more evident among the females. Furthermore, there was also a statistically signifi cant difference between different ages for both sexes. It was concluded that biological maturation is an important factor that should be considered when dealing with growth, but that it exhibits distinct behavior at different ages and in different sexes.